Understanding apple consumers’ expectations in terms of likes and dislikes. Use of comment analysis in a cross-cultural study - Galmarini, Mara Virginia (2013)
Apple consumers’ expectations in Argentina and France were studied by comment analysis of open-ended questions. In an on-line survey consumers stated: attributes which defined quality in an apple; visual, flavor and texture characteristics they liked/did not like to find in an apple. Influence of country, consumption frequency and cultivar knowledge were analyzed by contingency tables, Chi-square per cell tests and Multiple Factor Analysis. Consumers’ quality expectations were not the same in both countries. Argentineans and French consumers agreed that quality apples should be juicy (most used term in both countries), tasty, firm and fresh. However, for Argentineans quality was more related to visual characteristics, whereas for French it was driven by flavor. Argentineans used more words but French were more specific, particularly for flavour description. Moreover, frequency of consumption, varieties knowledge and the number of terms given were highly related. Frequent consumers knew more varieties and were more prolific in relation to flavour. Less frequent consumers knew fewer apple varieties and gave more words in the visual category. The use of comment analysis allowed identifying the terms that consumers used in their day to day life to describe apples, finding separately likes and dislikes, in spite of the different languages.